Peran Kepuasan Kerja dalam Meningkatkan Employee Engagement - Gilang Baskoro Widagdo; Yuli Budiati; Wyati Saddewisasi (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to analyze the role of job satisfaction in increasing employee engagement and examine the influence of transformational leadership, organizational support, and work-life balance on employee engagement, both directly and indirectly, through job satisfaction as a mediating variable among employees at the Semarang City Manpower Office. The research method used a quantitative approach with a survey technique, utilizing primary data obtained through a five-point Likert-scale questionnaire. The study population consisted of 92 employees, with a sample of 90 respondents determined using a census sampling technique. Data analysis was conducted using the Partial Least Squares–Structural Equation Model (PLS-SEM) method. The results indicate that transformational leadership, organizational support, and work-life balance have a positive and significant effect on job satisfaction and a positive and significant effect on employee engagement. Job satisfaction was also shown to have a positive and significant effect on employee engagement and significantly mediate the influence of transformational leadership, organizational support, and work-life balance on employee engagement. In conclusion, job satisfaction plays a strategic role in strengthening employee engagement. Therefore, improving leadership quality, organizational support, and work-life balance needs to be optimized to create sustainable employee engagement.   Keywords: Job Satisfaction, Employee Engagement, Transformational Leadership, Organizational Support, Work Life Balance